Phytopharmacology Studies of Ulmaceae (International Journal of Food and Nutritional Sciences, 2022)
In spite of recent advance in analytical techniques of modern medicine, in India and evenwestern countries the traditional medicine is still the major form of treating diseases of majorityof people. The number of people using one form or another of complementary of alternativemedicine is rapidly increasing worldwide. The family Ulmaceae included in core eudicots.Species form this family economically used as timber, making ropes and traditional medicine.Bioactive compounds of Ulmaceae are moderately strong accumulators of polyphenoliccompounds, derivatives of caffeic acid, catechins, pro-anthocyanidins, flavonols and condensedtannins seem to occur more or less ubiquiteous in leaves, fruits, barks and woods. The presentreview discussed about the phytopharmacology studies of family Ulmaceae.